Integrating patients' perceptions into clinical practice guidelines for the management of rheumatoid arthritis in Japan. Issue 6 (2nd November 2017) - Kojima, Masayo; Nakayama, Takeo; Otani, Takashi; Hasegawa, Mieko; Kawahito, Yutaka; Kaneko, Yuko; Kishimoto, Mitsumasa; Hirata, Shintaro; Seto, Yohei; Endo, Hirahito; Ito, Hiromu; Kojima, Toshihisa; et al.
Abstract: Objective: Patients' values and preferences are among the key factors that determine the strength of recommendations presented in clinical practice guidelines (CPG). The aim of this study was to summarize the integration process for patients' perceptions into the development of CPG for rheumatoid arthritis (RA) management in Japan. Methods: We used a mixed-methods approach. Questionnaires that could be self-administered were mailed to 2222 RA patients randomly selected from the Japan Rheumatism Friendship Association (JRFA) membership list that was age- and prefecture-stratified. A focus group with five JRFA executive members was formed to verify the results of the questionnaire. Results: A total of 1470 patients aged 20–79 years old returned the questionnaire. Analysis of the questionnaire data revealed that the topics selected by the CPG task force met the patients' needs. The focus group participants showed reluctance to use the term 'preference' because patients would not want to take any medications but would have to take them out of necessity. Conclusions: We confirmed that the new CPG successfully addressed clinical issues that were important to both rheumatologists and patients. Clinicians should understand patients' reluctance to take medications and explain the role of each medication well to increase adherence.